DOES THE VOLATILITY STRUCTURE OF DOUBLE REGISTERED STOCKS DIFFERENTIATE ACCORDING TO STOCK EXCHANGES? (Third Sector Social Economic Review, 2022)
This study was conducted to investigate the volatility structures and leverage effects of stocks listed on Borsa Istanbul (BIST) and traded in foreign markets at the same time. Daily frequency price data of six Turkish ADRs covering the period 01.01.2010 - 01.11.2021 were used in present analyses. The univariate asymmetric stochastic volatility model was applied and Markov Chain Monte Carlo was used as the estimation method. Each stock was modeled separately for both domestic and foreign markets and following findings were obtained: A volatility shock that will come to the stocks of all companies whose second registration is in OTC Market was found to be more permanent than in Borsa Istanbul (BIST). Negative shocks to stock volatility in OTC Market increased the volatility more than positive shocks as compared to BIST, so the leverage effect was more effective in OTC Market. The volatility of the stocks, whose second stock market record was in New York Stock Exchange (NYSE), was more predictable in BIST. In addition, the leverage effect of stock volatility in NYSE was not found to be significant.
Keywords: Double registered stocks; leverage effect; volatility structure; stochastic volatility model.